Sharia and Monarchs in Southeast Asia: Political Legitimation in Brunei Darussalam - Zada, Khamami; Arsadani, Qosim; Saepullah, Saepullah; Sugito, Mohamad Shofin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
In this modern era, sharia is still relevant in the monarchy system. Brunei Darussalam is a country that places sharia in a political monarchy that is prone to orthodoxy. This study analyzes the policy of implementing sharia in Brunei Darussalam in a monarchical political configuration. This study uses qualitative research that analyzes the phenomenon of the application of sharia in Brunei with a sociological and political approach. The research data comes from a number of documents in the form of the Brunei Constitution, Sharia Penal Code Order 2013 (SPCO), other royal regulations, and online media. Data collection was carried out using documentation techniques which were analyzed by applying the theory of political determination of law developed by Nonet and Selznick and the theory of legitimacy developed by Weber. This study found that the policy of implementing sharia in Brunei through SPCO, under a monarchical political system produced responsive legal products. This policy is based on the people's aspirations as a manifestation of the culture and religious practices of the people of Brunei. The implication is that international attacks on the implementation of sharia in Brunei have met with resistance from the people. The application of sharia nationally further strengthens the political legitimacy of the Sultan of Brunei in maintaining and preserving his power. The people were increasingly loyal to the Sultan, so there was social order without popular opposition.